Psychic euosmia and obsessive compulsive personality disorder - Pasquini, Massimo (World J Psychiatry, 2018)
Patients with obsessive compulsive personality disorder (OCPD) often refer to a prompt mood improvement upon encountering good scents in general, or fresh laundry borax on their clothes, pillows or home settings. The Authors propose the new term psychic euosmia in the mean of an overstated psychological predisposition for a real pleasant smell that elicits an immediate sense of pleasure, order and calm. The prompt reactions to a pleasant odor might be explained by the involvement of rhinencephalon and its proximity to mood-related limbic circuits, which bypass the cognitive awareness. Cleanliness may not preclude a subject to enjoy a good smell, even if we are representing smells that resemble freshness, in other words order. A potentially even more important argument is given by the continuum of personality disorders and their variability. Not all personality characteristics led to disturbed behaviors. In evolutionary perspectives having the ability to differentiate between unpleasant and pleasant odors should have made the difference in surviving. On the other hand, psychic euosmia could be considered a normal reaction, but in our clinical experience it is over-represented among OCPD subjects with marked orderliness and disgust. Therefore, detecting psychic euosmia might vicariously confirm the relevance of disgust as a cognitive driver of OCPD. Hereby we support research to characterize psychic euosmia as a feature of orderliness and cleanliness for OCPD.